A Low-Prevalence Single-Nucleotide Polymorphism in the Sensor Kinase PhoR in Mycobacterium tuberculosis Suppresses Its Autophosphatase Activity and Reduces Pathogenic Fitness: Implications in Evolutionary Selection - Waturuocha, Uchenna Watson; Krishna, M. S.; Malhotra, Vandana; Dixit, Narendra M.; Saini, Deepak Kumar (Frontiers in Microbiology, 2021)
The genome sequencing of Mycobacterium tuberculosis, the causative organism of tuberculosis, has significantly improved our understanding of the mechanisms that drive the establishment of infection and disease progression. Several clinical strains of M. tuberculosis exhibit SNPs, the implications of which are only beginning to be understood. Here, we examined the impact of a specific polymorphism in PhoR, the sensor kinase of the PhoPR two-component system. Biochemical analysis revealed reduced autophosphatase/ ATPase activity, which led to enhanced downstream gene expression. We complemented M. tuberculosis H37Ra with the wild-type and mutant phoPR genes and characterized the strains in a cell line infection model. We provide an explanation for the low prevalence of the SNP in clinical strains (~1%), as the mutation causes a survival disadvantage in the host cells. The study provides a rare example of selection of a signaling node under competing evolutionary forces, wherein a biochemically superior mutation aids bacterial adaptation within-host but has low fitness for infection and hence is not selected. Our study highlights the importance of accounting for such SNPs to test therapeutic and co-therapeutic methods to combat TB.